ANALYSIS OF THE COFFEE PEEL APPLICATION OVER THE SOIL-CEMENT BRICKS PROPERTIES - Castro, Eliziane Denize de; Villella, Luciana Silva; Mendes, Lourival Marin; Mendes, Rafael Farinassi; Ribeiro, André Geraldo Cornélio; Júnior, José Benedito Guimarães; Rabelo, Giovanni Francisco (Coffee Science - ISSN 1984-3909, 2019)
ANALYSIS OF THE COFFEE PEEL APPLICATION OVER THE SOIL-CEMENT BRICKS PROPERTIES ABSTRACT The development materials that use less polluting manufacturing techniques and can be manufactured from agricultural and / or industrial waste is an increasingly explored field of research. The objective of the present work was to study the effects of the coffee peel particles (Coffea arabica L.) incorporation in partial replacement of the cement, on the physical, mechanical and thermal properties of bricks, at different ages. For this purpose, soil was corrected with sand, Portland cement type CP II F-32 and coffee peel particles. After the initial percentage of cement in the mixture was defined as 10%, coffee peels were added in relation to cement, equal to 5%, 10%, 15% and 20%. The bricks were submitted to simple compression tests, at the ages of 14, 28 and 56 days, thermal insulation at 28 days. The increase in peel content caused increases in water absorption, and reduction of compressive strength and apparent specific dry mass. The interaction between the shell content and the age of the specimens was significant only for the variable resistance to compression. The thermal conductivity found for the material showed its insulating potential, with values below those determined for ceramic bricks. In general, it can be concluded that the material produced did not fit in the normative requirements for soil-cement bricks, however, the mechanical characteristics found in there, indicate the possibility of use in rustic constructions, such as those ones made with adobe bricks. Index Terms: Compressive strength, Durability, Thermal insulation, Vegetable particles. RESUMO O desenvolvimento de materiais que utilizem técnicas de fabricação menos poluidoras e que possam ser fabricados a partir de rejeitos agrícolas e/ou industriais é um campo de pesquisa cada vez mais explorado. O presente trabalho teve como objetivo estudar os efeitos da incorporação de partículas de casca de café (Coffea arabica L.), em substituição parcial ao cimento, sobre as propriedades físicas, mecânicas e térmicas de tijolos em diferentes idades. Para tanto, foi utilizado solo corrigido com areia, cimento Portland do tipo CP II F-32 e partículas de casca de café. Definido o percentual inicial de cimento na mistura em 10%, foram inseridos percentuais de casca de café, em relação ao cimento, iguais a 5%, 10%, 15% e 20%. Os tijolos foram submetidos aos ensaios de compressão simples, nas idades de 14, 28 e 56 dias, isolamento térmico, aos 28 dias. O aumento no teor de casca provocou acréscimos na absorção de água e redução da resistência à compressão e massa específica aparente seca. A interação entre o teor de casca e a idade dos corpos de prova foi significativa apenas para a variável resistência à compressão. A condutividade térmica encontrada para o material evidenciou seu potencial isolante, com valores abaixo dos determinados para tijolos cerâmicos. De um modo geral, pode-se concluir que o material produzido não se enquadrou nas exigências normativas para tijolos de solo-cimento, entretanto, as características mecânicas encontradas, indicam a possibilidade de utilização em construções rústicas, como as realizadas com tijolos de adobe.